Factors associated with sexual towards pre-marital sex activity - Abdullah, Fa’iza; Zainuddin, Nur Akmanidar; Draman, Samsul; A. Rahman, Nor Azlina; Muhammad, Noor Azimah (2019)
The consequences of adolescents in early involvement with sexual activity include sexually transmitted diseases, unwanted pregnancy, and unsafe abortion. The purpose of this study is to identify the socio-demographic and socio-cognitive factors (permissive attitude, social norms, and self-efficacy) associated with sexual intention to engage in premarital sex among school-going late adolescent in Kuantan, Pahang. A cross-sectional study was conducted in nine government secondary schools in Kuantan district between MarchJune 2018. A total of 466 self-administered validated Youth Sexual Intention Questionnaires (YSI-Q) data are collected among unmarried students aged 18-19 years-old. Statistical analyses were done using IBM SPSS version 22.0. Majority of the participants were females (64.4%), Muslims (68.2%) and Malays (67.4%). Simple logistic regression on sociocognitive factors showed for every one unit increase in permissive attitude, social norms and self-efficacy scores, there were 1.424, 1.303 and 1.215 times increase risk of having sexual intention, with p-value of 0.001 each and 95% CI of odds ratio OR) 1.268-1.600, 1.191-1.425 and 1.066-1.386, respectively. Multivariate logistic regression showed that female had lower risk of having sexual intention compared to male (p=0.001, OR=0.163, CI=0.058-0.462), Non-Malays had higher risk compared to Malay students and eversmokers had higher risk compared to non-smoker students towards having sexual intention with p=0.001, OR=5.110, CI=1.881-13.886 and p=0.019, OR=3.288, CI=1.218-8.875, respectively. In addition, for every unit increase in permissive attitude score, there was 1.236 times increase risk of having sexual intention with p=0.002 and 95% CI of OR=1.0841.410. In conclusion, the risk of having sexual intention was found to be higher among males, non-Malay and ever-smoker students; and also among those with higher permissive attitude scores. Therefore, further study and peer education intervention programs are required for school-going students to improve their permissive attitude and to prevent risk